2017
DOI: 10.3889/oamjms.2017.054
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extended Typing On Red Blood Cell Alloimmunization in Transfused Patients

Abstract: BACKGROUND:Red blood cell (RBC) alloimmunization is still an actual problem in our transfusion practice. In 2011, in addition to the regular ABO/D blood group typing, phenotyping for Rh (C, c, E, e) and Kell antigens was introduced for blood donors and patients undergoing blood transfusion. Our aim was to evaluate the impact of the extended RBC typing and donor/recipient matching on the incidence of RBC alloimmunization.METHODS:A retrospective comparative study was conducted by reviewing RBC request records fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…Approximately half of these patients receive multiple transfusions throughout their lives, and approximately 7·5% begin a system of chronic transfusion (Zheng & Maitta, ). However, this therapy can be associated with an increased risk of hyperhemolysis, transient aplasia and erythrocyte alloimmunisation (Miller et al ., ; Kelly et al ., ; Makarovska‐Bojadzieva et al ., ).…”
mentioning
confidence: 97%
“…Approximately half of these patients receive multiple transfusions throughout their lives, and approximately 7·5% begin a system of chronic transfusion (Zheng & Maitta, ). However, this therapy can be associated with an increased risk of hyperhemolysis, transient aplasia and erythrocyte alloimmunisation (Miller et al ., ; Kelly et al ., ; Makarovska‐Bojadzieva et al ., ).…”
mentioning
confidence: 97%
“…This frequency is far inferior to the one obtained in Morocco by Atouf in 2013 which was 90.4%, also in Ivory Coast carried by Sekongo in 2017 the obtained a frequency of 28.6%. This can be explained by the difference in the total population of study which was 2027 in Morocco by Atouf,42 in Ivory Coast compare to us which was 104 [5,16]. These results obtained implies that in the future, sickle cell patient will have difficulty in finding compatible blood for treatment and it is a real problem since transfusion is the major standard of care for patient suffering from sickle cell anemia in Cameroon.…”
Section: Discussionmentioning
confidence: 73%
“…Shah et al and Setya et al reported similar results of the frequencies [24,25]. However, Makarovska-Bojadzieva et al from the Republic of Macedonia reported different results with low frequencies of both Jka and Jkb at 7.7% and 2.5% respectively [26].…”
Section: Discussionmentioning
confidence: 82%